Tipo de cambio real y ventaja absoluta de costo: Espa\~na, 2000-2014 - Fahd Boundi Chraki (Investigación Económica, 2019)
– This research is aimed to test the hypothesis that the real effective exchange rate between Spain's manufacturing sectors and its European Union partners has been governed by the relative vertically integrated unit labor costs and the intrasectoral differences of the profit rate during 2000-2014. Using panel cointegration techniques, the results suggest that there exists a stable long-run relationship between those three variables. Likewise, cointegration vectors indicate that the Spanish manufacturing competitiveness is positively associated with the decrease in unit costs of production, while it is negatively related to the increase in the intrasectoral profitability gap.
Keywords: B51; C01; F10; F20; 330; Spain; European Union; panel cointegration; competitiveness; uneven development